Encouraging Landscape Water-Conservation Behaviors #5: Segmenting the Audience Based on HOA Status - Laura A. Warner; Alexa J. Lamm; Emmett Martin; Joy N. Rumble; Esen Momol (EDIS, 2016)
The newest article in the Encouraging Landscape Water-Conservation Behavior series, this 6-page fact sheet provides Extension professionals with information on segmenting audiences based on their home owner association status. It provides data that shows how HOA membership potentially affects the barriers that households face when adopting conservation measures and explains how Extension professionals should use this information to enhance programming by strategically planning programs based on the similarities between clients. Written by Laura A. Warner, Alexa J. Lamm, Emmett Martin, Joy N. Rumble, and Esen Momol, and published by the Department of Agricultural Education and Communication, April 2016.